Development of an enterprise decision platform: Service-Oriented Architecture approach. (5th April 2010) - Yuen, Kevin Kam Fung
Group decision making activities have been applied in many domains in the enterprises. As many decision algorithms can be used for various domains and one domain can use various decision algorithms, this paper proposes an Enterprise Decision Platform (EDP) for the development of the adaptive decision applications. EDP is the intelligent multi-agent framework which embeds the decision algorithms as intelligent agents, and applies the architecture concept of Service Oriented Architecture (SOA) which is implemented by web-services. An application development of Intelligent Supplier Evaluation System (ISES) demonstrates how this proposed model functions.